Digital Transformation of Basic Education: Current Situation, Dilemmas and Countermeasures - Tian, Xinling (Transactions on Social Science, Education and Humanities Research, 2024)
Digitization is a global trend, and in the current context of information technology, and education, as a part of which is shown, its digital transformation is necessary. Supported by such a background, this study draws the current situation based on the digitalization of education at the current stage by reading the literature. It is found that the digital transformation of education at this stage faces several dilemmas, and this paper is a targeted discussion of the lack of teachers’ digital technology skills and the communication problems of online education, it is found that the main reasons are the lack of teachers’ training in digital technology, the unequal distribution of teaching resources, and the fact that online courses are not face-to-face teaching. This study addresses these issues by proposing training for teacher teams before new technologies are introduced to campuses and the use of AR and VR technologies to create real classrooms.